Pengembangan Media Pembelajaran Interaktif Tata Rias Foto Berwarna dan Hitam Putih pada Mata Kuliah Tata Rias Ditinjau dari Validasi Ahli Media: Penelitian - Fairaz Haya Sriashita; Titin Supiani; Nurul Hidayah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to develop interactive learning media for color and black and white photo makeup in the Makeup course. The development process follows the research and development model with the ADDIE model which has stages of needs analysis, design, development, implementation, and evaluation. The resulting learning media contains material, learning videos and interactive quizzes designed to be easily accessible and interesting for students. Validation was conducted by media experts to assess the feasibility and quality of the media. The results of the validation test showed that the Canva-based interactive learning media obtained a score of 96%, which was included in the category of very feasible to use as learning media in the Makeup course. This finding shows that the media developed effectively supports the learning process and student understanding of color and black and white photo makeup material.